2021
DOI: 10.1016/s2665-9913(20)30238-1
|View full text |Cite
|
Sign up to set email alerts
|

Serious postoperative complications and reoperation after carpal tunnel decompression surgery in England: a nationwide cohort analysis

Abstract: Background Carpal tunnel decompression surgery to treat carpal tunnel syndrome is a common procedure, yet data on safety and effectiveness of the operation in the general population remain scarce. We aimed to estimate the incidence of reoperation and serious postoperative complications (requiring admission to hospital or further surgery) following carpal tunnel decompression in routine clinical practice and to identify the patient factors associated with these adverse outcomes. Methods We did a nationwide coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…A low complication rate (1.4%) was reported after surgery for CTS, the most common peripheral neuropathy. 10,11) The complication rate after surgery for LFCN-E was 0-5%; hematomas and wound issues were common. 12) In an earlier series, 13) 12% of TTS operations were followed by complications; they were noninfected wound dehiscence that healed.…”
Section: Discussionmentioning
confidence: 99%
“…A low complication rate (1.4%) was reported after surgery for CTS, the most common peripheral neuropathy. 10,11) The complication rate after surgery for LFCN-E was 0-5%; hematomas and wound issues were common. 12) In an earlier series, 13) 12% of TTS operations were followed by complications; they were noninfected wound dehiscence that healed.…”
Section: Discussionmentioning
confidence: 99%
“…None of our patients reported any complications, and none of them required reoperation within the period of observation. A cohort analysis by Lane et al ( 24 ) conducted in an English population (855 832 initial surgeries) showed a very small rate of serious complications requiring hospitalization or further surgery equalling <0.1% (incidence rate: 1 per 1,000 per year).…”
Section: Discussionmentioning
confidence: 99%
“…Carpal tunnel decompression appears to be a safe operation in most patients, with an overall serious complication rate (requiring admission to hospital or further surgery) of less than 0.1% [40]. Serious complications include surgical site infection or dehiscence, or neurovascular or tendon injury.…”
Section: Complicationsmentioning
confidence: 99%